Impact of Experiential Learning Strategy on Secondary School Students’ Academic Achievement in Computer Studies in Nnewi Education Zone, Anambra State - Muogbo Uchenna Favour; Okafor U. Theresa; Okafor Chinyere Francisca (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: The impact of Experience-Based Learning (EBL) on the academic achievement of secondary school students in Computer Science in the Nnewi Education Zone, Anambra State, Nigeria, has become an important issue that needs to be addressed. Objective: The study aims to assess the effect of the Experiential Learning Strategy (ELS) on the academic achievement of secondary school students in Computer Studies. Method: A quasi-experimental design with a pretest-posttest non-equivalent control group was used. Eighteen community secondary schools were selected from 48, with two schools randomly chosen. Intact classes participated, where students were taught Microsoft Word using either ELS or the traditional lecture method (LM). The Computer Studies Achievement Test (CSAT) was used for data collection, and data were analyzed using mean, standard deviation, and ANCOVA. Results: Results showed a significant difference in achievement scores, favouring students taught with the Experiential Learning Strategy (ELS). Conclusion: The study recommended incorporating the Experiential Learning Strategy into the curriculum as a teaching strategy for Computer Studies in the classroom, as it fosters self-development. Contribution: This study provides empirical evidence of ELS's effectiveness in improving academic achievement, offers a framework for enhancing student engagement in Computer Studies, and suggests future directions for integrating innovative teaching strategies into education.